2021
DOI: 10.2217/fon-2020-1265
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Levels of Breast Cancer Patients in Turkey During the COVID-19 Pandemic

Abstract: Aim: To assess the anxiety levels of breast cancer patients during the COVID-19 pandemic. Materials & methods: A total of 298 patients completed the State-Trait Anxiety Inventory (STAI-S and STAI-T) and the Visual Analogue Scale for Anxiety (VAS) and VAS for Anxiety in COVID-19 (VAS-CoV). Results: 144 patients were in the high anxiety category for STAI-S, and 202 patients were in the high anxiety category for STAI-T. STAI-T score was significantly high in the metastatic group (p = 0.017). VAS-CoV score in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…The results of this qualitative study were consistent with the results of previous quantitative research, showing that patients with cancer experienced more anxiety and distress during the COVID-19 pandemic (Ciążyńska et al, 2020;Sigorski et al, 2020;Yasin et al, 2021;Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this qualitative study were consistent with the results of previous quantitative research, showing that patients with cancer experienced more anxiety and distress during the COVID-19 pandemic (Ciążyńska et al, 2020;Sigorski et al, 2020;Yasin et al, 2021;Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…COVID‐19 and the aforementioned changes or delay in cancer care can influence the psychological well‐being of patients and their relatives. In various countries, the effect of COVID‐19 on the well‐being of patients with cancer was investigated using a survey (Baffert et al, 2021 ; Ballatore et al, 2021 ; Chapman et al, 2020 ; Choobin et al, 2021 ; Ciążyńska et al, 2020 ; Ferrara et al, 2021 ; Jeppesen et al, 2021 ; Cheli et al, 2021 ; Swainston et al, 2020 ; Wang et al, 2020 ; Yasin et al, 2021 ). Several of these studies suggest a potentially higher risk for psychological distress and anxiety among patients with cancer during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has detrimental effects on the lives of cancer patients due to the uncertainty regarding treatment and screening, combined with the fear of being infected ( Gregucci et al, 2020 ; Brivio et al, 2021b ). Several studies have reported considerably high levels of anxiety, depression, and post-traumatic stress disorder ( Beaty et al, 2018 ; Chen et al, 2020b , 2021 ; Sigorski et al, 2020 ; Swainston et al, 2020 ; Ayubi et al, 2021 ; Yasin, 2021 ), and increased emotional vulnerability ( Pigozzi et al, 2021 ). In some cases, respondents were cancer patients undergoing treatment at the time of the study ( Sigorski et al, 2020 ; Chen et al, 2021 ), but active treatment status was not always among the inclusion criteria (e.g., Swainston et al, 2020 ; Yasin, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported considerably high levels of anxiety, depression, and post-traumatic stress disorder ( Beaty et al, 2018 ; Chen et al, 2020b , 2021 ; Sigorski et al, 2020 ; Swainston et al, 2020 ; Ayubi et al, 2021 ; Yasin, 2021 ), and increased emotional vulnerability ( Pigozzi et al, 2021 ). In some cases, respondents were cancer patients undergoing treatment at the time of the study ( Sigorski et al, 2020 ; Chen et al, 2021 ), but active treatment status was not always among the inclusion criteria (e.g., Swainston et al, 2020 ; Yasin, 2021 ). The vast majority of surveys were administered online and assessed patients’ psychological health ( Chen et al, 2020b ; Romito et al, 2020 ; Sigorski et al, 2020 ; Swainston et al, 2020 ; Yasin, 2021 ) and their fear of tumor progression ( Chen et al, 2020b ; Sigorski et al, 2020 ) during the first wave of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation